Kekhilafahan Islam, Globalisasi dan Gerilya Maya: Studi Kasus Hizbut Tahrir Indonesia - Setia, Paelani; Rahman, M. Taufiq (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
This paper aims to explain the role of radical Islamic organizations in the era of globalization. The case study taken in this research is Hizbut Tahrir Indonesia (HTI). As a transnational organization, Hizb ut-Tahrir grew and crossed national boundaries, including arriving in Indonesia and playing an essential role in shaping public opinion in Indonesia. This study uses qualitative research methods to collect data through online observation, which is described by content analysis. The findings of this study are Hizb ut-Tahrir Indonesia is part of the players of globalization. This is evidenced by the organization's involvement in 50 countries and five continents globally supported by their global media. In Indonesia, although the Government disbanded it in 2017, Hizb ut-Tahrir's activities are still strengthened and maintained through globalization instruments such as the internet. HTI then carried out virtual guerrilla activities to keep the idea of a caliphate grounded.